HALAL MSMEs DEVELOPMENT MODEL THROUGH THE APPLICATION OF BUSINESS COMPETITION FIQH - Abdul Hadi Ismail; Khairunnisa Khairunnisa (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
One of the main problems that occur in the development of halal MSMEs is the complex and expensive halal certification process. This study aims to obtain a halal MSME development model through business competition fiqh. This research will also later explore related to the fiqh of business competition which is not widely known by Halal MSMEs. The research method used is quantitative description. The result 1) tstatistic 3.932> 1.96, P value of 0.000 <0.05 (Significant) then Marketing, has no effect on the development of Halal MSMEs. 2) t-statistic 0.630 < 1.96, Pvalue 0.592 > 0.05 (Not Significant) then Digital literacy and product innovation have no effect on the development of Halal MSMEs. 3) H3: X3 Against Y = t-statistic 2.902> 1.96, Pvalue 0.004 <0.05 (Significant) then product innovation has an effect on the development of Halal MSMEs. 4) Then Z against Y = t-statistic 1.310 < 1.96, pvalue 0.191 > 0.05 (Not Significant) . MRA (Moderated Regression Analysis): 5) H5 : X1*Z on Y: -0.056 (negative / weakening), pvalue 0.529 > 0.05 (Not Significant) then Fiqh of Business competition does not play a role in moderating the marketing relationship with the development of Halal MSMEs. 6) H6 : X2 * Z to Y: 0.090 (positive, pvalue 0.281> 0.05 (Not Significant) then Fiqh competition does not play a role in moderating the relationship between digital literacy and the development of Halal MSMEs. 7) H7: X3 * Z to Y: -0.087 (positive, pvalue 0.064> 0.05 (Not Significant) then Fiqh competition does not play a role in moderating the relationship between Product Innovation and the development of Halal MSMEs.